Experimental Study on Characteristics of Energy Storage Defrosting and Conventional Defrosting for Cascade Air Source Heat Pump - Qu Minglu; Li Tianrui; Fan Yanan; Wang Tan (Zhileng xuebao)
Based on the frosting and defrosting problems of cascade air source heat pumps (CASHPs) during heating operation in the cold area in winter, a novel thermal energy storage CASHP defrosting system with a thermal accumulator is proposed. The defrosting performances of thermal energy storage defrosting mode with intermittent heating and continuous heating were experimentally studied, and then the experimental results were compared with common used hot-gas bypass defrosting mode. It was found that in energy storage defrosting mode, the defrosting duration time and the energy consumption were reduced by 71.4%~77.6% and 65.1%~85.2% respectively compared with hot-gas bypass defrosting mode, and the system defrosting operation was more stable and reliable.